2011
DOI: 10.4318/tjg.2011.0323
|View full text |Cite
|
Sign up to set email alerts
|

Serum iron parameters in cirrhosis and chronic hepatitis: Detailed description

Abstract: p<0.001). Changes in ferritin and transferrin saturation were essentially opposite to this trend (r=0.3, p=0.01 and r=0.47, p<0.001, respectively

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
17
4

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 18 publications
10
17
4
Order By: Relevance
“…group (p<0.05) ( Table 4). This agrees with the study of Ibrahim et al [1] and Buyukasik et al [20], who both found a decrease level of total iron binding capacity in patient as compared with control group as mentioned previously that total iron binding capacity reflects transferrin activity and the later produced in liver and its production decrease liver damage [20].…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…group (p<0.05) ( Table 4). This agrees with the study of Ibrahim et al [1] and Buyukasik et al [20], who both found a decrease level of total iron binding capacity in patient as compared with control group as mentioned previously that total iron binding capacity reflects transferrin activity and the later produced in liver and its production decrease liver damage [20].…”
Section: Discussionsupporting
confidence: 82%
“…this is in agreement with the work of Ibrahim et al [1] who found an increase in serum iron level in chronic liver disease patients as compared with control group, also the study in agreement with Lin et al [2] who found an increased iron level in chronic hepatitis B infection as compared with control group, in contrast to other studies Buyukasik et al [20] and Mahmood et al [21] who both found that there was no significant difference in serum iron level in chronic liver disease patients and control groups . group (p<0.05) ( Table 4).…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Hepacivirus. patients (6) . The present study showed an increase in the serum levels or positive correlation with CTP or BCLC in transferrin (in CI group), iron (in CI and HCC group) and ferritin saturation (in HCC group), which is in accordance with the literature (11,28,30,38) .…”
Section: Discussionmentioning
confidence: 99%
“…An elevated TS level in a patient without liver dysfunction is a sensitive biochemical indicator for IO [12][13] .Clinical algorithms for detection of IO usually start with this test. In this study, we found that serum iron tests compatible with iron overload are not infrequent in MM at diagnosis.…”
Section: Discussionmentioning
confidence: 99%